Quality testing of industrially produced essential oil of white pine (Pinus sylvestris L.) from the Republic of Srpska - Marjanović-Balaban, Željka; Gojković Cvjetković, Vesna; Kapović-Solomun, Marijana; Stanojević, Ljiljana; Stanojević, Jelena; Kalaba, Vesna (Journal of Engineering & Processing Management, 2020)
The quality of the essential oil obtained from white pine wood greenery from the territory of the Republic of Srpska was analyzed by examining the chemical composition and antimicrobial activity of samples produced by the hydro-distillation process in industrial production conditions. The chemical composition of the essential oil was analyzed by GC/MS and GC/FID analysis. The antimicrobial activity of the obtained white pine oil was investigated for its possible use as an antimicrobial agent. The obtained results prove the presence of 37 components in the analyzed sample, which represents 98.5% of the total components present. The most common are monoterpene hydrocarbons, followed by sesquiterpene hydrocarbons, much less represented are monoterpenes containing oxygen and aromatic compounds, while aliphatic esters are found only in traces. Antimicrobial activity was examined using the disk diffusion method. The results showed large zones of inhibition, both for the tested oil sample and for all eight analyzed bacterial strains (from 12.00 ± 0.00 to 17.33 ± 1.15mm), as well as for the fungal strain. The chemical composition and antimicrobial action of essential white pine oiled from plant material originating from the territory of the Republic of Srpska indicates its significant phytomedical potential.